The specificity and scope of European Union finance law - Marcin Tyniewicki (Prawo Budżetowe Państwa i Samorządu, 2015)
Basically, Polish science of financial law quite broadly takes the problems concerning public finance of the European Union (EU). However, it should be noticed that the considerations largely refer to the detailed issues within the confines of individual branches of EU financial law, eg. in areas of tax harmonization or single financial market. At the same time there is an insufficiency or even minuteness publications with doctrinal and theoretical nature referring to the general and fundamental issues of financial law of the EU. There may be numbered such issues among others as definitions, scope and internal structure of this law, its legal sources etc. Generally two areas should be object of the basic scientific researches in reference to the issues mentioned above. First one is financial law of the EU and the second one – its influence and effect of this influence on Polish financial law. In this article there will be undertaken considerations referring to the first area aimed at defining the specifity and scope of EU financial law.